Introduction to Daily Prayers Through the Art of Singing at Tk Aba Kanganyar - Joko Pamungkas; Septika Cahya Rahmawati (International Journal of Educational and Psychological Sciences, 2024)
This research aims to describe how singing is an alternative in introducing daily prayer at the Aba Karanaganyar Kindergarten. Aba Karanganyar Kindergarten is part of an Aisyiyah organization which has a mission in education, namely teaching monotheism, one of which is by memorizing daily prayers. This type of research uses qualitative research with a descriptive approach. Data collection in this research included interviews, observation and documentation. The results of this research show that singing is an effective approach in teaching daily rote prayers. The stages in the process of getting used to singing are 1) the teacher introduces the prayer song that will be taught, 2) the child imitates it piece by piece or in faithful verse according to the tune. , 3) the teacher adds verses and starts combining them with other verses and the children imitate, 4) the teacher sings the whole song together with the children.